Intravoxel incoherent motion imaging used to assess tumor microvascular changes after transarterial chemoembolization in a rabbit VX2 liver tumor model - Cheng, Zhimei; Qin, Huanrong; Cao, Wei; He, Huizhou; Zhang, Shuling; Yang, Yushi; Wang, Zhenmin; Zou, Xun; Wang, Lizhou; Huang, Xueqing; Zhou, Shi; Zhang, Shuai (Frontiers in Oncology, 2023)
Purpose To evaluate the correlation between microvascular density (MVD) and intravoxel incoherent motion (IVIM) magnetic resonance imaging (MRI) parameters and the effect of glycolytic flux after transarterial chemoembolization (TACE) in a rabbit VX2 liver tumor. Materials and methods VX2 liver tumor allografts in 15 New Zealand white rabbits were treated with sterile saline (control group, n = 5) or lipiodol-doxorubicin emulsion (experimental group, n = 10). MRI was performed 2 weeks after the procedure to evaluate IVIM parameters, including apparent diffusion coefficient (ADC), pure diffusion coefficient (D), pseudodiffusion coefficient (D*), and perfusion fraction (PF). All animal samples were taken of the tumor and surrounding liver. Immunostaining for CD31, CD34, CD105, and VEGF was used to evaluate MVD. The protein expression of Glut4, HK2, PKM2, LDHA, and MCT1 was determined using western blotting. Pearson correlation tests were used to analyze the relationship between MVD and IVIM parameters. Results D* value in the peritumoral region was negatively correlated with CD34 (r = –0.71, P = 0.01). PF value positively correlated with CD34 (r = 0.68, P = 0.015), CD105 (r = 0.76, P = 0.004) and VEGF (r = 0.72, P = 0.008) in the peritumoral region. Glut4, HK2, PKM2, and MCT1 in the peritumoral regions were higher in the experimental group than in the control group (all P < 0.05). Conclusion IVIM parameters were correlated with MVD in the intratumoral and peritumoral regions after TACE in a rabbit liver tumor model. The angiogenesis reflected by MVD may be related to changes of glycolytic flux.